2011
DOI: 10.1245/s10434-011-1620-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Free Cancer Cells from the Gastric Lumen and from Perigastric Lymphovascular Pedicles during Radical Gastric Cancer Surgery

Abstract: Free cancer cells can be released from gastric lumen or lymphovascular pedicles opened during gastric cancer surgery, especially in advanced-stage disease. Care should be taken to minimize spillage from the gastric lumen and lymphovascular pedicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 29 publications
3
64
1
Order By: Relevance
“…Additionally, cancer cells can be released directly from the gastric lumen, which suggests that other contributing factors may also play a role both in iatrogenic tumor diffusion induced by surgery and in metastasis in the peritoneal cavity [9].…”
mentioning
confidence: 99%
“…Additionally, cancer cells can be released directly from the gastric lumen, which suggests that other contributing factors may also play a role both in iatrogenic tumor diffusion induced by surgery and in metastasis in the peritoneal cavity [9].…”
mentioning
confidence: 99%
“…Their findings suggest that the use of distilled water is associated with significantly increased rates of tumor lysis in mice models of colorectal cancer cell intraperitoneal spillage. Moreover, the results of a recent innovative study by Han and colleagues suggested that inappropriate surgical technique during radical gastrectomy and lymph node dissection may be the causative factor in spilling malignant cells into the peritoneal cavity via the gastric lumen or poorly sealed lymphovascular pedicles [42]. Following this, the only ongoing randomized phase III trial to evaluate the prognostic value of EIPL in addition to standard treatment in gastric cancer is the Japanese CCOG 1102 study by Misawa et al [43], whereby this multi-institutional study aims to recruit 300 patients with resectable gastric cancer (including cytology positiveonly disease).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Yang et al (15), by conducting ex vivo experiments on surgical specimens, demonstrated that if lymphovascular channels are not properly sealed, free cancer cells are spilled out. Therefore, during lymphadenectomy for gastric cancer, dissection with scissors or scalpel which may cause the opening of vessels, should be avoided, moreover all the visible lymphovascular vessels should be carefully closed with the use of clips or though energy-based devices (15).…”
Section: Additional Notesmentioning
confidence: 99%